(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
With India’s growing per capita income the lifestyles are also changing in a rapid way. After primary and secondary economic activities, the economic growth engine of the country is now in the hands of retail sector, which changes its landscape into a bigger form contains everything under one roof – shopping mall. This transformation of Indian retail sector has successful evidents in metropolitan cities as well as small towns. This paper tries to understand the changes in urban spaces due to this new retail transformation on Asansol Municipal Corporation of Paschim Bardhaman district of West Bengal. The present study is based on primary as well as secondary sources of data. The results have explained both in quantitative and qualitative methods. The study reveals that consumers are now becoming more brand conscious, comfort seeking and quality biased, at the same time they want to save their time. As a growing industrial urban center, Asansol is evolving with the new retail trend, as a result the urban space is changing and people attract more towards this new trend- Shopping Mall Culture.